2022
DOI: 10.1117/1.jbo.27.9.095002
|View full text |Cite
|
Sign up to set email alerts
|

Model-based characterization platform of fiber optic extended-wavelength diffuse reflectance spectroscopy for identification of neurovascular bundles

Abstract: . Significance: Fiber-optic extended-wavelength diffuse reflectance spectroscopy (EWDRS) using both visible/near-infrared and shortwave-infrared detectors enables improved detection of spectral absorbances arising from lipids, water, and collagen and has demonstrated promise in a variety of applications, including detection of nerves and neurovascular bundles (NVB). Development of future applications of EWDRS for nerve detection could benefit from the use of model-based analyses includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Computational simulations offer a powerful approach to understand individual tissue layers contribution to the overall measurement. Computational simulations include Monte Carlo (MC) modelling, which have been utilized previously to model fiber optic spectroscopy to simulate spectra from tissues [7,9]. A study of skin-bone models indicated MC simulations could enable the decomposition of overall signals into layer-based contributions [7].…”
Section: Introductionmentioning
confidence: 99%
“…Computational simulations offer a powerful approach to understand individual tissue layers contribution to the overall measurement. Computational simulations include Monte Carlo (MC) modelling, which have been utilized previously to model fiber optic spectroscopy to simulate spectra from tissues [7,9]. A study of skin-bone models indicated MC simulations could enable the decomposition of overall signals into layer-based contributions [7].…”
Section: Introductionmentioning
confidence: 99%